INTER-STUDENTS’ LANGUAGE POLITENESS OF SMP NEGERI 2 KELAYANG INDRAGIRI HULU - Titi Yustia Siregar; Mangatur Sinaga; Charlina Charlina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper describes and analyzes the language politeness among students of SMP Negeri 2 Kelayang Kelayang District in Indragiri Hulu Regency. It is qualitative research using an analytical descriptive method, namely analyzing and exposing data found in the form of words. Data analysis techniques begin with data reduction, presentation, and making conclusions and verification of the data. The data collection techniques carried out are recording, listening, and taking notes techniques. The source of the research data is inter-student speech. Based on the research results, it was found that the forms of language politeness compliance were the obedience of the maxim of wisdom, the obedience of the generosity maxim, the obedience of the praise maxim, the obedience of the humility maxim, the obedience of the agreement maxim, and the obedience of sympathy maxim. In addition to the obedience of language politeness, violations of language politeness were also found, namely violations of the maxim of wisdom, violations of the generosity maxim, violations of the praise maxim, violations of the humility maxim, violations of the agreement maxim, and violations of the sympathy maxim. The dominant maxim is the violation of the maxim of praise. In addition to the violation of the praise maxim, a dominant maxim refers to obedience to the generosity maxim.